The Chemical Basis of Intracerebral Hemorrhage and Cell Toxicity With Contributions From Eryptosis and Ferroptosis - Derry, Paul J.; Vo, Anh Tran Tram; Gnanansekaran, Aswini; Mitra, Joy; Liopo, Anton V.; Hegde, Muralidhar L.; Tsai, Ah-Lim; Tour, James M.; Kent, Thomas A. (Frontiers in Cellular Neuroscience, 2020)
Intracerebral hemorrhage (ICH) is a particularly devastating event both because of the direct injury from space occupying blood to the sequelae of brain exposed to free blood components from which it is normally protected. Not surprisingly, the usual metabolic and energy pathways are overwhelmed in this situation. In this review, we detail the complexity of red blood cell degradation, the contribution of eryptosis leading to hemoglobin breakdown into its constituents, the participants in that process and the points at which injury can be propagated such as elaboration of toxic radicals through the metabolism of the breakdown products. Two prominent products of this breakdown sequence, hemin and iron, induce a variety of pathologies including free radical damage and DNA breakage, which appear to include events independent from typical oxidative DNA injury. As a result of this confluence of damaging elements, it is likely that multiple pathways of injury, cell death and survival are engaged including ferroptosis (which may be the same with oxytosis but viewed from a different perspective) and senescence, suggesting that targeting any single cause will likely not be a sufficient strategy to maximally improve outcome. Combination therapies in addition to safe methods to reduce blood burden should be pursued.